Kádár - Muszatics, Péter (Hungary, 2009)
Portrait of János Kádár (1912-1989), the Hungarian communist leader and the General Secretary of the Hungarian Socialist Workers' Party who presided over the country from 1956 until 1988. This film traces his career via speeches, interviews and his famous last speech.